Conceptual foundations of qualitative life course research - Heinz, Walter R. (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2016)
Analyzing biographies is a main field of qualitative social research that studies individuals’ sensemaking in regard to transitions and life projects. The paper presents concepts for linking the macrosocial and micro-social levels in life course analysis. First, the concept of “status passage” is reviewed, with a focus on social structure, institutions, and biography. Second, the concept of “selfsocialization” is introduced, highlighting the notion of the “biographical actor”. Third, recent elaborations of the concept of “agency” in life course research are discussed. Fourth, two examples of qualitative longitudinal research are presented: one on occupational careers, another on the process of family formation. Finally, methodological implications are sketched.